Engendering Democracy in Africa Women, Politics and Development - Gaynor, Niamh (Routledge Studies in African Development, 2022)
This book investigates women's political participation in Africa. Going beyond the formal institutions of electoral politics, it explores a range of spaces where everyday politics take place, at national and at local levels. In recent years there have been significant improvements in the number of women elected to parliament in Africa. However, there is little indication that this is translating into better developmental outcomes, and indeed there is mounting evidence that it could in fact help to bolster some authoritarian regimes. Starting from the premise that politics is a far broader project than securing a seat in national or local legislatures alone, this book explores the opportunities for women's political participation across a number of informal spaces where women and men gather, organise and interact in a more regular and systematic manner. Combining insights from political science, sociology and feminist theory and drawing on detailed cases from the Congo, Kenya, Malawi, Nigeria and Rwanda, it examines how power in its multiple dimensions circulates across a range of everyday political spaces, while drawing attention to the links between domestic gender inequalities and the global political economy. Inviting scholars, practitioners and activists to broaden their focus beyond formal electoral institutions if they want to support women to become more politically active, this book provides fresh insights into major issues at the heart of African studies, development studies, gender and development, democratisation, and international relations.